PELATIHAN PENGGUNAAN WEBSITE DESA BAGI PARA STAFF DI DESA BANJARSARI, KABUPATEN TANGGAMUS - Erliyan redy; Jupriyadi Jupriyadi; neneng neneng; Rio A. M. Putra; ARNIZA FITRI (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2022)
Rapid developments of technology in education, business, office administration, government and information dissemination play an important and large role in human life as a whole. The internet as a supporting tool can be a source of information in finding information related to various activities. Banjarsari village has quite large natural potential such as plantations, agriculture and tourism, but not much is known by people outside the village. The Village Website is expected to be a means of disseminating information, supporting superior village programs and publishing matters related to the potential that exists in Banjarsari village. Until now, the knowledge of the community or sub-district staff in Banjarsari village regarding the use of the website is still very lacking, so that the dissemination of village information through the website has never been implemented. In this PKM activity, the PKM team from the Indonesian Technocrat University helped develop a village website in Banjarsari village. Apart from that, the UTI PKM team also held training for all staff in Banjarsari village in order to be able to manage the website that had been created. With the creation and training of using the website in Banjarsari village, it is hoped that village programs and information about the village can be accessed and socialized properly.